O etnodesign aliado ao design escandinavo na moda masculina contemporânea - Chagas, Izabela Fernanda (2017)
As a consequence of the needs and desires of contemporary consumer society, fashion is understood as a means of communicating new social values, breaking patterns that no longer contextualize society. In pursuit of individuality and identity, the present monograph is based on the exploratory research of the Etnodesign tool and the principles of Scandinavian Design, with the aim of developing a collection of men's fashion that rescues and improves the craft techniques in contemporary design, simple and functional. The information collected supported the base of the field of quantitative research content and in the development of the marketing direction of the brand, reflecting positively the needs and preferences of the target audience analyzed, and promoting, in addition to breaking the existing stereotypes in society regarding craftsmanship in men's fashion, the orientation towards the formation of a Brazilian market identity integrates.